The Congruence-Novelty Paradox: Exploring the Effects of Self-congruence and Novelty on Memorable Tourist Experiences - Kitin, Justin James (Curtin University, 2023)
This research examined the impact of self-congruity and novelty-seeking on memorable tourist experiences. It aimed to understand the individual influences of self-congruity and novelty-seeking, as well as compare their relative strengths in shaping memorable tourist experiences. Additionally, the research investigated the moderating effects of cultural distance and uncertainty avoidance on these relationships.